EVALUASI PELAKSANAAN PENGELOLAAN SAMPAH DI BANK SAMPAH KECAMATAN SUKUN KOTA MALANG - Rachmat Ardiyan; Winarko .; Demes Nurmayanti (GEMA LINGKUNGAN KESEHATAN, 2013)
Solid waste to be have economic value after have been sorted and while good processedas already proved by trash bank in Malang city which invite the peoples to segregate the wastefrom it's source and come to the bank to make a deposit based on their waste's value. Thisresearch purposed to evaluate waste management implementation in Trash Bank of Malangcity.Method of this research according the data analysis included descriptive research naturewith cross sectional approach. Object of this research in Malang Trash Bank is located in S.Supriyadi street number 38A on Sukun district of Malang city. Data taken subsequently will beanalyzed descriptively based on tabulation of result from observation sheet and assessmentsheet.The results of this research showed that quantity of rubbish was accepted by MalangTrash Bank about 2500 Kg/day and 75% majority rubbish source come from household type.Requirements of building's construction and trash bank of standard management taken fromthe result of assessment which had meeting the standard (92%) of requirements refer inRegulation of State Minister of the Environment number 13/2012. Work's mechanism in MalangTrash Bank achieved good criteria (85,3%). Supporting factors of waste managementimplementation was planned and executed.It is suggested to the Malang Trash Bank is necessary to add number of worker andtransportation vehicle for picking up rubbish from customers or delivery ready to sale rubbish tocollector and industry. Make cooperation with figures people, cadre environment, or rubbishbusinessmen in community empowerment particularly process to separate rubbish and keepenvironment cleanliness.Keywords : Evaluation, Waste Management and Trash BankPEND